Phytochemical, Physiochemical, Macroscopic, and Microscopic Analysis of Rosa damascena Flower Petals and Buds - Zead Helmi Abudayeh; Uliana Karpiuk; Narjes Armoon; Qais Abualassal; Eyad Mallah; Loay Khaled Hassouneh; Yousef Aldalahmeh (Journal of Food Quality)
Macroscopic and microscopic analysis of R. damascena buds and flower petals was used to find the main morphological and anatomical features of these types of medicinal plant material (MPM). The presence of polysaccharides, free and bound monosaccharides, tannins, flavonoids, saponins, and essential oils was confirmed by chemical and histochemical reactions. The quality indicator of R. damascena buds and flower petals was evaluated in this study; weight loss on drying gave the next result: 6.69 ± 0.20% for flower petals and 6.65 ± 0.13% for buds. The swelling index showed a high result for R. damascena flower petals and buds. R. damascena buds swelling index—5 ± 0.2 and R. damascenaflower petals swelling index—15 ± 0.6. The determination of volatile substances by GC/MS shows the presence of 18 volatile compounds in flower petals and buds, this number varies up to 17. Nonadecane, heneicosane, and octadecane are the main components in both medicinal plant materials. Both buds and flower petals contain approximately the same amount of citronellol. Phenylethyl alcohol is present in large amounts in buds but in small amounts in flower petals. R. damascena flower petals and buds are the sources of volatile compounds, phenols, and polysaccharides. The results of our investigation showed great differences and similarities between buds and flower petals of R. damascena. We have confirmed that not only buds but also flower petals could be a source of biologically active substances (BASs) such as essential oils, polysaccharides, and phenolic compounds. Flower petals could be an alternative MPM. We would also like to underline the importance of standard documentation for MPM: its macro and microscopic description, harvest time, control techniques of the qualitative composition, and the quantitative content of the main BAS. Because it will help in the production of various high-quality products that can be used in medicine, pharmacy, food, and the perfume industries.